Personality Factors in English Language Learning: Inhibition, Anxiety and Risk –Taking - Turg`unboyeva Maxliyo Ikrom qizi (Zien Journals, 2022)
This paper is an attempt to look at individual personality factors as the importance variables in the second language acquisition from a theoretical approach. To accomplish the goals of this paper, the definition of the concepts and the importance of each personality factor such as motivation, attitude, acculturation, self-esteem, sociability, risk-taking and perseverance which lead to greater proficiency in the second language acquisition are discussed in a brief but broad overview. Generally, this paper aims at drawing attention to the role of individual personality factors in a second language acquisition process from an Islamic point of view. It is hoped that with such knowledge, language teachers could promote and allow the development of learners’ personalities, and at the same time, are able to take possible actions in cases when special guidance and help are required. We told above that personality factors' types. Now, We are going to know about inhibition, anxiety, risk -taking
Keywords: Personality factors; Second language acquisition; Target language; risk -taking